Trafficking of children for sexual exploitation : public international law 1864-1950 - Rao, Sunil Salankey (New Delhi : Oxford University Press, 2013)
Sunil Rao examines the development of public international law from 1864 to 1950 in relation to the trafficking of children for sexual exploitation of prostitution. He provides an account and examination of the formation of each treaty adopted during this period, and demonstrates the progressive conceptual development of public international law in this area by analysing each treaty in the areas of gender, race, administrative and legal measures, description of the act of trafficking and connection between the act of trafficking and the exploitative end purpose of prostitution.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Child prostitution; Child trafficking; Children (International law)